Corporate Accountability for Contractor Deviations in Construction Payment Claims: Legal, Ethical, and Governance Perspectives - Arief Koeswanto; Prastiwo Anggoro; Sarwono Hardjomuljadi; Ediyanto Arief; Sami’an; Achmad Soeharto (Universitas Serang Raya, 2026)
The Indonesian construction industry is central to national infrastructure and economic development, yet construction projects remain vulnerable to contractual, ethical, and governance risks. This article examines corporate accountability for contractor payment-claim deviations in an Indonesian construction project, focusing on the interaction between contract law, professional ethics, Good Corporate Governance, and ISO 9001:2015-based quality management. The study adopts a normative juridical approach combined with a qualitative single-case analysis of a chemical plant construction project in East Java that used a modified FIDIC contract. Primary materials comprise contract clauses, invoice and Interim Payment Certificate records, supporting claim documents, project correspondence, and professional observations, while secondary materials include Indonesian construction-law regulations, FIDIC-related literature, and scholarship on fraud prevention and construction claims. The case indicates that payment-claim deviations were associated with premature or inadequately supported claims, inconsistencies between claimed and verified work progress, and weaknesses in documentation and verification controls. The analysis shows that payment claims operate as legal-contractual events and governance-control events, requiring clear entitlement, reliable evidence, engineer verification, and an auditable approval trail. Fraud-risk concepts are used to interpret how opportunity, rationalization, capability, and organizational ethical orientation may normalize irregular claims. The study argues that accountability should be strengthened through clearer claim documentation, risk-based internal controls, ethical leadership, DAAB institutionalization, simplified EoT/VO procedures, and safeguards against contractual power asymmetry.